Intra-session and Inter-day Reliability of the Myon 320 Electromyography System During Sub-maximal Contractions - Sorbie, Graeme G.; Williams, Michael J.; Boyle, David W.; Gray, Alexander; Brouner, James; Gibson, Neil; Baker, Julien S.; Easton, Chris; Ugbolue, Ukadike C. (Frontiers in Physiology, 2018)
Electromyography systems are widely used within the field of scientific and clinical practices. The reliability of these systems are paramount when conducting research. The reliability of Myon 320 Surface Electromyography System is yet to be determined. This study aims to determine the intra-session and inter-day reliability of the Myon 320 Surface Electromyography System. Muscle activity from fifteen participants was measured at the anterior deltoid muscle during a bilateral front raise exercise, the vastus lateralis muscle during a squat exercise and the extensor carpi radialis brevis (ECRB) muscle during an isometric handgrip task. Intra-session and inter-day reliability was calculated by intraclass correlation coefficient, standard error of measurement and coefficient of variation (CV). The normalized root mean squared (RMS) surface electromyographic signals produced good intra-session and inter-day testing intraclass correlation coefficient values (range: 0.63–0.97) together with low standard error of measurement (range: 1.49–2.32) and CV (range: 95% Confidence Interval = 0.36–12.71) measures for the dynamic-and-isometric contractions. The findings indicate that the Myon 320 Surface Electromyography System produces good to fair reliability when examining intra-session and inter-day reliability. Findings of the study provide evidence of the reliability of electromyography between trials which is essential during clinical testing.